Occupational stress and its impacts on employee performance: a case study of Hwange Colliery Company limited, Zimbabwe. - Chikumbindi, Lenah (Midlands State University, 2018)
The study sought to assess impact of occupational stress on employee performance at Hwange Colliery Company Limited. The study aimed at Identifying sources of occupational stress, determining the impact of occupational stress on employee performance, as well as examining the strategies to curb occupational stress on employee performance. The research employed quantitative (Questionnaires) and qualitative (interviews) research methods. The research established that job insecurity, safety issues, unhealthy work sites, delays in the payment of salaries and benefits as well as lack of recognition for outstanding work done were the main causes of stress. The research also established that workers who are married and divorced were mostly affected by home pressure and recorded high levels of work stress. The study concluded that occupational stress has negative impact to the organizational performance as it resulted in lost time injuries, absenteeism, accidents, low morale and poor work relations. The study recommends proactive interventions by implementing management strategies that aims on elimination of occupational stress so that the organization may fully achieve optimum organizational excellence. Institutional coping strategies were found to be fragmented, weak and almost non-existent. Proper environmental management at the work sites, outstanding performance recognition, down to top approach in decision making, provision of adequate PPE, stress management training and adoption of employee wellness and assistance programs were the main recommendations brought forward to improve the workers’ welfare and reduce the levels of occupational stress at Hwange Colliery Company Limited.